KESIAPAN INFRASTRUKTUR PUSKESMAS TAMPAKSIRING I KABUPATEN GIANYAR BALI DALAM MENGIMPLEMENTASIKAN PROGRAM JKN - Riskadewi Agatha (DiscoverSys Inc., 2015)
Background: Program JKN, demanding public health centers as firstâ€line to provide adequate facilities. Community health center infrastructure readiness Siring I became one of the points that need to be considered to assess the readiness of health centers in the era of JKN. Purpose: The purpose of this study was to determine the readiness of Sukawati I PHC infrastructure in implementing JKN system. Methods: This was a descriptive research studies on qualitative. This study was conducted to examine the PHCinfrastructure readiness in implementing the Sukawati I JKN. It is seen by direct observation of the infrastructure and inâ€depth interviews Results: Building Health Center Sukawati I still do not meet the standard because although the building has a permanent and meet safety standards and ease of service delivery and the protection and safety of all persons, including persons with disabilities, children, and the elderly. Building clinics have not noticed the building function and comfort. This is evidenced by the presence of an improper use of the room. One common example is, immunization activities are often carried out in the employee break room while the health center already has a separate room for immunization activities. In addition to the immunization room lighting is less than the maximum. From the nonâ€building health center has 2 ambulances, 1 car mobile health clinics, a medical waste / nonâ€medical, emergency medical equipment, consumables, and sterilizer, but there is a shortage in the availability of emergency medicine and drug standards to handle 144 diseases that must be completed in PPK1 level. In addition there are constraints on the availability of laboratory equipment. From this study, it can beconcluded that a prominent factor in the implementation of infrastructure in health centers JKN Sukawati I nongedung facilities and buildings that are still not memadahi.